Quantitative research on health determinants in high-income countries: Systematic literature review. (13th November 2019) - Varbanova, V; Beutels, P
Abstract: Background: Identifying determinants of health and understanding their role in health production is an important research theme. In recent decades data have become more accessible and multi-country analyses offer an appealing way to potentially enrich such research. Methods: We followed the PRISMA guidelines to systematically identify, triage and review literature published between 2013 and early 2018. Forty-three studies that performed cross-national statistical analyses aiming to evaluate the impact of one or more aggregate level determinants on one or more general population health outcomes in high-income countries were selected out of an original yield of 7353. To assess in which combinations and to what extent individual (or thematically linked) determinants had been studied together, we performed multidimensional scaling and cluster analysis. Results: Life expectancy and overall mortality were the most widely used population health indicators, while determinants came from the broad categories of healthcare, culture, politics, socio-economics, environment, labor, fertility, demographics, life-style, and psychology. The family of regression models was the predominant statistical approach. Results from our multidimensional scaling showed that a relatively tight core of determinants have received much attention, whereas most others were studied in very limited contexts. We consider research findings inconclusive at this time: across a multitude of model specifications, different country samples, and varying time periods, effects fluctuated between statistically significant and not, and between beneficial to health and detrimental. Conclusions: We conclude that the quest to understand the underlying mechanisms of population health is far from over and the present state of research on the topic leaves much to be desired. It seems essential that future research always considers multiple factors simultaneously and takes advantage of more sophisticated methodology. Key messages: Provides a broad overview of the current state of research on the topic of determinants of population health in high-income countries. Employs an innovative approach examining the degree to which context has been taken into account, as a basis for future research.